2004
DOI: 10.1093/qjmed/hch135
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life preferences in elderly patients admitted for heart failure

Abstract: Advance planning of end-of-life procedures and doctor-patient communication regarding these items remains poor and must be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 33 publications
0
62
0
6
Order By: Relevance
“…ACP remains uncommon. 9,65,105,[140][141][142][143] National surveys report no strong resistance to or discomfort about talking about death among the public. 65,134 However, despite sustained campaigns to encourage public and professional engagement in ACP, only 5-6% of respondents have documented their preferences for EOLC.…”
Section: Uptake and Initiation Of Advance Care Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…ACP remains uncommon. 9,65,105,[140][141][142][143] National surveys report no strong resistance to or discomfort about talking about death among the public. 65,134 However, despite sustained campaigns to encourage public and professional engagement in ACP, only 5-6% of respondents have documented their preferences for EOLC.…”
Section: Uptake and Initiation Of Advance Care Planningmentioning
confidence: 99%
“…Evidence accumulates about the complex situational factors underlying decisions and the varied preferences which may subsequently be expressed. 22,59,66,69,142,180 The focus on place has deflected attention from how death is experienced in different settings. 69,72,73,77,179 Patients tend to adopt a pragmatic stance to place of death.…”
Section: 132139mentioning
confidence: 99%
“…The care context, in which 'cure' is the goal, may present an important barrier to engaging clinicians and individuals in inherently time-consuming conversations about quality-of-life and endof-life planning and care, with which they may be far less comfortable. In addition, a review of cardiovascular deaths in one Canadian metropolitan health region suggested that few patients with CVD died at home or in hospice (J Brown, personal communication), despite evidence suggesting that 50% to 75% of patients with HF would, if given the opportunity and support, choose to die at home (25). While this may not mean we need to increase the number of patients who die at home, all patients at the end of life should have access to support and comfort in the location of their choice.…”
Section: Care Contextmentioning
confidence: 99%
“…However, there are indications that the disease symptoms often fluctuate in patients with non-cancer illnesses, such as end-stage chronic obstructive pulmonary disease (COPD) or heart failure, and the course of the disease is therefore difficult to predict. [3][4][5] It can be expected that the shift towards palliative care in these patients may only take place shortly before death and that identifying a time point for transition to palliative care is more difficult for people with COPD, for instance. 6 The course of the disease in patients with incurable cancer maybe relatively predictable, with a clearer demarcation between the curative and palliative stages.…”
Section: Introductionmentioning
confidence: 99%